The Association Between Concurrence of Infection and the Onset of Severe Eruption or Liver Injury in Patients Using Antipyretic Analgesics: A Matched, Nested Case‐Control Study. (10th June 2020) - Imatoh, Takuya; Sai, Kimie; Saito, Yoshiro
Abstract: Stevens‐Johnson syndrome (SJS) and toxic epidermal necrosis (TEN) or drug‐induced liver injury (DILI) are severe drug‐induced reactions, known as idiosyncratic drug reactions. It is believed that immune response can lead to these severe adverse drug reactions. Our previous analysis of the Japanese Spontaneous Drug Reaction database suggested that the onset of SJS/TEN and DILI was strongly associated with infection. Hence, we conducted a matched, nested case‐control study to elucidate the association between concurrent infection and the onset of SJS/TEN or liver injury in patients prescribed antipyretic analgesics. We extracted 4 112 055 patients who were prescribed antipyretic analgesics between January 2014 and December 2015. Amongst them, 553 (0.01%) were diagnosed with SJS/TEN and 12 606 (0.3%) with liver injury. In a matched, nested case‐control study, 131 and 2847 cases matched for SJS/TEN or liver injury, respectively. For each case, 3 controls were randomly matched with the case for age at index date and sex. In the conditional logistic regression analysis, there was a significant association between the combination of infection and antipyretic analgesics and the onset of SJS/TEN or liver injury (SJS/TEN: adjusted OR, 5.59; 95%CI, 2.01‐15.51; liver injury: adjusted OR, 2.79; 95%CI, 2.24‐3.46). Although it was not possible to distinguish whether the associations were caused by the infection or were a direct consequence of the antibiotic agents, our findings may help to increase awareness of the possibility of the increased onset of idiosyncratic drug reactions (SJS/TEN and liver injury) in antipyretic analgesic users because of infections.